FEMALE EPISPADIAS: SPOT DIAGNOSIS AND SIMPLE RECONSTRUCTION - Nawaz, Gul; Muhammad, Shujah; Jamil, Muhammad Imran; Rehman, Asad Ur; Khawaja, Muhammad Athar; Hussain, Ijaz; Akber, Mian Khalid; Akhter, Saeed (Journal of Ayub Medical College Abbottabad, 2014)
Isolated female epispadias without bladder exstrophy is a rare congenital anomaly. Patients present with total or partial urinary incontinence. The diagnosis can only be made on careful genitalia examination by separating the labia majora. That is why it is often missed by most physicians even after being extensively investigated. The physical findings include patulous urethra, flattened mons pubis, and bifid clitoris with lack of anterior labial commissure. In most of the cases, single stage reconstruction of urethra, labia minora and clitoris is enough to achieve urinary continence with cosmetically acceptable genitalia. Keywords: Female epispadias, urinary incontinence, single stage repair